Transformasi Digital di Pesantren: Kolaborasi Pengabdian Masyarakat Menuju Pesantren Cerdas - Rudianto Rudianto; Munawaroh Munawaroh; April Laksana; Kenedi Kenedi; Ardiyansah Ardiyansah; Anisa Pramitasari; Pretty Failasufa Aziza; Kiki Setyawati; Sari Ningsih; Indri Yani; Imam Rozikin; Denardo Denardo; Anisa Kusumawardani; Abdul Chatim Pramono; Yuwan Ditra Krahara; Harsiti Harsiti; Agus Irawan; Mohamad Hilman; Iqbal Fernando; Ahmad Fatoni (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
Community service represents one of the fundamental contributions of academics to social development, particularly in the educational sector. This article elaborates on the implementation of a community engagement program entitled Towards Smart Pesantren through Digital Transformation, conducted on May 28, 2025, at SMA Bi’rul Ulum Cisait, Serang, Banten. The initiative emerged from an inter-university collaboration aimed at enhancing the digital capacities of santri (Islamic boarding school students) to better prepare them for the challenges of the digital age. The program focused on training in graphic design, public speaking, an introduction to artificial intelligence (AI), and human resource development (HRD) in the digital context. Methods employed in the program included lectures, interactive discussions, and hands-on practice, allowing participants to gain both theoretical understanding and practical skills. The participatory approach fostered active engagement and created an enriching learning environment. Evaluation results indicated a high level of enthusiasm among the participants and a marked improvement in their grasp of fundamental digital competencies. This program exemplifies the strategic potential of inter-institutional academic collaboration in supporting the digital transformation of pesantren-based education in Indonesia. It is expected that the initiative can serve as a replicable and sustainable model for future community service efforts in similar educational contexts, particularly in promoting 21st-century skills.